2020
DOI: 10.1002/jbm.b.34741
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of femtosecond laser and air‐abrasion protocols to monolithic zirconia at different sintering stages: Effects on surface roughness and resin bond strength

Abstract: This study aimed to investigate the effects of femtosecond laser (Fs) and/or air‐abrasion protocols on surface roughness (Ra) of zirconia and resin bond strength. Eighty zirconia samples were randomly divided into eight subgroups according to surface treatment protocols: Control (C), Air‐abrasion before sintering (ABS), Air‐abrasion after sintering (AAS), Air‐abrasion before and after sintering (ABS + AAS), Fs laser before sintering (FBS), Fs laser before sintering + air‐abrasion after sintering (FBS + AAS), F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 50 publications
4
21
1
4
Order By: Relevance
“…Akın et al reported that CO2 laser irradiation of zirconia might be an ineffective method for improving the bond strength of resin cement to zirconia 19) . Er:YAG and Nd:YAG laser treatments have been proposed to improve the bond strength to zirconia 19,22) . In this study, the bond strength data proved that ytterbium fiber laser irradiation was more efficient at increasing the bond strength of resin cements to zirconia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akın et al reported that CO2 laser irradiation of zirconia might be an ineffective method for improving the bond strength of resin cement to zirconia 19) . Er:YAG and Nd:YAG laser treatments have been proposed to improve the bond strength to zirconia 19,22) . In this study, the bond strength data proved that ytterbium fiber laser irradiation was more efficient at increasing the bond strength of resin cements to zirconia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have examined laser surface treatment to improve the surface modification of titanium and zirconia implant bodies 12,13) . Laser treatment can cause various changes in material surfaces, including creating proper surface roughness to increase the bonding of resin cements to zirconia, which is difficult to manufacture with high hardness [18][19][20][21][22][23][24] . It has been also recognized that ytterbium laser treatment on zirconia surfaces enhances the bond strength between zirconia and resin cements 23) .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 A proportionally larger area has a high surface energy, which can improve mechanical bonding to the zirconia surface. 9,18 Airborne particle abrasion has gained popularity with regard to obtaining roughness on the zirconia surface, 23 but conflicting results were reported in some related studies. 8,24,25 In many studies applying surface treatment, where SBS and surface roughness were evaluated, there was no correlation between the SBS values and the surface roughness values.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the translucent zirconia surface obtained following the FSL treatment presented uniform irregular structures without groove-like structures or pits, as confirmed in the SEM image shown in Figure 2e. Surface topography can be modified by femtosecond laser surface treatment and surface roughness of the zirconia can be increased; thus, the bond strength can be improved [31].…”
Section: Discussionmentioning
confidence: 99%